1996
DOI: 10.1071/rj9960351
|View full text |Cite
|
Sign up to set email alerts
|

Event-Driven or Continuous; Which Is the Better Model for Managers?

Abstract: Over the past ten years or so, discussion of vegetation change in rangeland science has emphasised event- driven or episodic processes, occurring on timescales measured in decades or longer. Management recommendations arising from this literature have stressed that management must also be event-driven. This paper cautions against the uncritical acceptance of such a world view into management philosophies. We conclude that for management purposes, appropriate models of change in rangeland systems should include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…We have acknowledged this tension in the past, and understand that what we learn from science is provisional and we will continue to learn. 18 At issue here is the reconciliation of existing scientifi c evidence with a perceived understanding accumulated from either personal or generational experiences, or accumulated over time at specifi c sites.…”
Section: Discussionmentioning
confidence: 99%
“…We have acknowledged this tension in the past, and understand that what we learn from science is provisional and we will continue to learn. 18 At issue here is the reconciliation of existing scientifi c evidence with a perceived understanding accumulated from either personal or generational experiences, or accumulated over time at specifi c sites.…”
Section: Discussionmentioning
confidence: 99%
“…Major concerns included strategies for communication using models and their role in management; the ability (or inability) to define quantitatively both states and transitions for specific plant communities; and incorporation of spatial processes, such as water flow (Brown 1994;Grice and MacLeod 1994;Scanlan 1994). Shortly afterward, Watson et al (1996) questioned the strong focus on event-driven processes and abrupt change and suggested that a model of more continuous, cumulative change was just as appropriate to describe vegetation dynamics in many systems. Further, they suggested an emphasis on the management of vegetation within an ecological state to either prime it for a desired transition or protect it from an undesired transition.…”
Section: Historymentioning
confidence: 99%
“…These events may occur infrequently or unpredictably, which can lead to uncertainty about the extent and frequency of monitoring required to encapsulate the full range of event characteristics and associated ecological responses. Further, their effects on receiving waters are often superimposed on seasonal or inter-annual changes in receiving-water quality and ecology, all of which require management consideration that is underpinned by detailed scientific understanding [1]. In addition, poor land use decisions are more likely to be made during long dry spells (e.g., encroachment of urban areas into floodplains), unpredictable flow events may occur when farmed floodplains are most vulnerable to erosion (e.g., when they have been recently plowed and seeded), and infrastructure such as levees and channelization that are implemented to deal with extreme flows can destabilize channels, leading to further problems during high flow events.…”
Section: Ecological Management Of Receiving Waters In Event-driven Ecmentioning
confidence: 99%